2023
DOI: 10.5603/fm.a2022.0078
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and morphometric features of sacral hiatus and its clinical significance in caudal epidural anaesthesia

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…15 In the present study, base of sacral hiatus was most found at level of 5 th sacral vertebra. This was similar to many studies [16][17][18] which also found hiatal base at level of 5 th sacral vertebra in 98.6%, 75.19% and 89.03% of dry human sacral bones. However, the present study did not find statistically significant difference in level of base between cases and controls.…”
Section: Discussionsupporting
confidence: 92%
“…15 In the present study, base of sacral hiatus was most found at level of 5 th sacral vertebra. This was similar to many studies [16][17][18] which also found hiatal base at level of 5 th sacral vertebra in 98.6%, 75.19% and 89.03% of dry human sacral bones. However, the present study did not find statistically significant difference in level of base between cases and controls.…”
Section: Discussionsupporting
confidence: 92%